2017
DOI: 10.1515/mms-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Analysis of Partial Discharge using an Ultra-High Frequency Sensor for Gas Insulated Structures

Abstract: Although the gas insulated structures have a high degree of reliability, the unavoidable defects are primary reason of their failures. Partial discharge (PD) has been regarded as an effective indication for condition monitoring and diagnosis of gas insulated switchgears (GISs) to ensure their reliable and stable operation. Among various PD detection methods, the ultra-high frequency (UHF) technique has the advantages of on-line motoring and defect classification. In this paper, there are presented 7 types of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…By contrast, in the back propagation, errors calculated by comparing actual output and desired output propagate from output layer to input layer with update of weights and biases. The back propagation algorithm continuously operated until the allowable error was less than 0.0001 and then the trained weights were updated in the system for real-time lightning warning [17][18][19]. This intelligent algorithm was developed based on the LabVIEW program with the standard state machine design pattern.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…By contrast, in the back propagation, errors calculated by comparing actual output and desired output propagate from output layer to input layer with update of weights and biases. The back propagation algorithm continuously operated until the allowable error was less than 0.0001 and then the trained weights were updated in the system for real-time lightning warning [17][18][19]. This intelligent algorithm was developed based on the LabVIEW program with the standard state machine design pattern.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…This is because SF 6 has an exceptional combination of physical and chemical properties for high-voltage applications, including high-dielectric strength (three times that of air at atmospheric pressure), arc-quenching capability, thermal conductivity, thermal stability, nonflammability, nontoxicity, nonexplosive, and chemical inertness [1][2][3][4]. As a result, SF 6 -insulated equipment can be designed with reduced size, high reliability, and economic efficiency [5,6]. It is widely employed in space-limited locations such as city substations, offshore plants, or wind-power plants [7].…”
Section: Introductionmentioning
confidence: 99%
“…The global warming potential (GWP) of SF 6 is 23,500 times that of carbon dioxide (CO 2 ) over a 100-year time horizon and is 32,600 times that of CO 2 over a 500-year time horizon. The atmospheric lifetime of SF 6 is 3200 years, whereas that of CO 2 is only 30-90 years [1]. It was reported that 1 kg of SF 6 released into the atmosphere has the equivalent global warming impact as 23.5 tons of CO 2 [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in the field of GIS state detection, experts from various countries are devoted to the study of characterization, detection methods, and prevention techniques of partial discharges in GIS. A real-time measurement system for partial discharge defect strength based on phase decomposition was developed by using an ultra-high frequency sensor [9]. A partial discharge sensor diagnosis method based on a silicon photomultiplier (SiPM) was proposed [10]; it promotes the partial discharge process of optical detection from laboratory simulations to practical applications.…”
Section: Introductionmentioning
confidence: 99%